In silico Molecular Docking Studies of 1,2,4 Triazole-norfloxacin Hybrids with Topoisomerase II as Potent Antitubercular Agents - ARUN PATIDAR; GAJANAND ENGLA (The Bioscan, 2025)
Tuberculosis remains a prevalent issue in global public health, necessitating the development of new anti-tubercular medications. In this study, molecular docking techniques were utilized to explore the potential of 1,2,4 triazole-norfloxacin hybrids as inhibitors of MtTopo II. Utilizing BIOVIA Software, simulations were performed to predict the binding modes and affinities of these hybrids within the active site of MtTopo II. The compounds that designed were assessed for their binding ability to the DNA gyrase target. The molecular docking performed using LibDockScore function indicated compounds N11, N10, N6, N52, N48, N9, N38 and N14 to exhibit promising binding affinity (LibDock score 128.77, 127.73, 124.47, 122.10, 119.84, 119.17, 118.49 and 117.07 respectively) when compared to the reference norfloxacin (LibDock score 106.20) with the target 5BTC (topoisomerase II). The results emphasize the efficacy of docking studies in rational drug design against tuberculosis, with the objective of advancing novel therapeutic approaches to combat TB.